Emotional Intelligence In Improving Children's Academic Achievement : A Review Of Development Psychology - Basri, Hasan; Intani, Trya Mia; Ririn, Ririn; Putri, Afrira Esa (Psikologiya Journal, 2025)
This study aims to examine the relationship between emotional intelligence and children's academic achievement using the literature study method from a developmental psychology perspective. This study reviewed 30 scientific articles obtained from the Scopus, ScienceDirect, and Google Scholar databases, with a publication range between 2013 and 2023. This method was chosen to gather relevant empirical evidence and strengthen the understanding of the contribution of intelligence to the academic emotional success of elementary school-aged children through adolescence. Inclusion criteria included publications containing quantitative or qualitative data on the influence of emotional intelligence on learning outcomes, academic engagement and social interactions in lin. Research was conducted using a thematic approach to identify consistent patterns of relationships in the literature. The results show that children with high emotional intelligence are better able to manage academic pressure, demonstrate good social skills and have high motivation to learn, which together contribute to improved academic performance. The study also emphasizes the importance of integrating emotional intelligence development in the education curriculum, as part of a holistic approach to learning. This research not only outlines the contribution of emotional intelligence to academic achievement, but also provides a basic concept for educational interventions that focus on the balance between cognitive and emotional aspects of development.